Modification of Zeolite Made from Coal Fly Ash with TiO2: Effect of Aging Time on Physical and Optical Properties - Kusumawardani, Linda Jati; Iryani, Ani; Sinaga, Ennita Lusiana (Makara Journal of Science, 2023)
The high levels of metal oxides, SiO2, and Al2O3 give coal fly ash the potential for development into zeolite. Zeolite was prepared from fly ash by combining alkaline fusion with hydrothermal treatment. Using this method results in a high surface area, high mechanical properties, and high crystallinity of the sample. Zeolite as a product is modified by TiO2. This study was intended to determine the effect of the operating process in zeolite synthesis from coal fly ash on the types and properties of zeolite and the effect of the aging time of TiO2-modified zeolite at 14, 16, and 20 h. Investigating its physical and optical properties shows that the product contains zeolite X as the major phase. The zeolite X itself contains 96% crystallinity and a specific surface area of 164.78 m2/g. Meanwhile, TiO2/zeolite increases the light absorption in the visible region. Diffuse reflectance spectroscopy showed that a 14 h aging time results in the lowest band gap energy of 2.50 eV and the largest surface area of 189.483 m2/g. X-ray diffraction characterization found that TiO2/zeolite is an anatase crystal (~9 nm) with 99% crystallinity. A pilot examination of the photodegradation performance of the TiO2/zeolite nanocomposite was evaluated using 5 mg/L methylene blue and compared with that of zeolite alone.